2021
DOI: 10.3390/jcm10245914
|View full text |Cite
|
Sign up to set email alerts
|

Headache Worsening after COVID-19 Vaccination: An Online Questionnaire-Based Study on 841 Patients with Migraine

Abstract: Vaccines have represented the breakthrough in the fight against COVID-19. Based on reported headache attacks after vaccination in randomized controlled trials, we focused on the effects of COVID-19 vaccine administration on the migraine population, using an online questionnaire published on Italian Facebook groups oriented to headache patients. We collected data about the demographics and clinical parameters of migraine severity, COVID-19 infection, vaccination, and characteristics of headaches following vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
20
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 35 publications
6
20
0
3
Order By: Relevance
“…Increased headache duration and pain intensity, as well as increased need to intensify preventive treatment after COVID-19 vaccine administration has also been previously reported in patients with pre-existing primary headache disorders including migraine (36-38). Silvestro M. et al also showed that most patients perceived the headache attacks as "different" from those usually experienced, being characterized by higher pain intensity, longer duration, and reduced responsiveness to usually effective analgesic treatment (39). In our study, headache pattern change was predominantly reported shortly after a vaccine administration, although with much lower frequency than acute symptomatic headache related with COVID-19 or during the pandemic overall.…”
Section: Covid-19 Vaccinationsupporting
confidence: 52%
“…Increased headache duration and pain intensity, as well as increased need to intensify preventive treatment after COVID-19 vaccine administration has also been previously reported in patients with pre-existing primary headache disorders including migraine (36-38). Silvestro M. et al also showed that most patients perceived the headache attacks as "different" from those usually experienced, being characterized by higher pain intensity, longer duration, and reduced responsiveness to usually effective analgesic treatment (39). In our study, headache pattern change was predominantly reported shortly after a vaccine administration, although with much lower frequency than acute symptomatic headache related with COVID-19 or during the pandemic overall.…”
Section: Covid-19 Vaccinationsupporting
confidence: 52%
“…In studies of COVID-19 vaccine, migraine-like features were present in one third of the cases (pulsating quality, phonophobia, and photophobia), and in 40-60% of the cases aggravation with activity was observed [68]. Interestingly, in a cohort of individuals with prior diagnosis of migraine, over half perceived the post-vaccination headache attacks as "different" from those usually experienced; this included higher pain intensity, longer duration, and reduced responsiveness to usually effective painkillers [80].…”
Section: Characteristics Of Post-vaccination Headachementioning
confidence: 99%
“…(97) collected data about headache after four different vaccinations (BNT162b2 67.3%, AZD1222 19.5%, mRNA-1273 11.1%, Janssen 2.1%) from 841 patients with migraine. A total of 66.5% of patients reported headache after the first COVID-19 vaccine, and 57.6% reported different features compared to those usually experienced, 52.8% reported a longer duration and 50.6% higher pain intensity (97). Headache during COVID-19 or that following influenza vaccination also showed a significant association with headache following COVID-19 vaccination (ORs = 4.3 and 4.84).…”
Section: Secondary Headaches and Covid-19mentioning
confidence: 99%